Seasonal Upwelling Conditions Modulate the Calcification Response of a Tropical Scleractinian Coral - Carlos E. Gómez; Andrés Acosta-Chaparro; Cesar A. Bernal; Diana I. Gómez-López; Raúl Navas-Camacho; David Alonso (Oceans, 2023)
Natural processes such as upwelling of deeper-water masses change the physical-chemical conditions of the water column creating localized ocean acidification events that can have an impact on the natural communities. This study was performed in a coral reef system of an archetypical bay within the Tayrona National Natural Park (PNNT) (Colombia), and aimed to quantify net calcification rates of a foundational coral species within a temporal context (6 months) taking into account the dynamics of seasonal upwelling that influence the study area. Net calcification rates of coral fragments were obtained in situ by the alkalinity anomaly technique in short-term incubations (~2.5 h). We found a significant effect of the upwelling on net calcification rates (Gnet) (p < 0.05) with an 42% increase in CaCO3 accretion compared to non-upwelling season. We found an increase in total alkalinity (AT) and dissolved inorganic carbon (DIC) with decreased aragonite saturation (Ωara) for the upwelling months, indicating an influence of the Subtropical Under Water mass (SAW) in the PNNT coral community. Significant negative correlations between net calcification with temperature and Ωara, which indicates a positive response of M. auretenra with the upwelling conditions, thus, acting as “enhancer” of resilience for coral calcification.